2018
DOI: 10.1152/ajplung.00430.2017
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species induced Ca2+influx via TRPV4 and microvascular endothelial dysfunction in the SU5416/hypoxia model of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a lethal disease characterized by elevations in pulmonary arterial pressure, in part due to formation of occlusive lesions in the distal arterioles of the lung. These complex lesions may comprise multiple cell types, including endothelial cells (ECs). To better understand the molecular mechanisms underlying EC dysfunction in PAH, lung microvascular endothelial cells (MVECs) were isolated from normoxic rats (N-MVECs) and rats subjected to SU5416 plus hypoxia (SuHx), an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 65 publications
10
87
0
Order By: Relevance
“…Human PAECs exposed to prolonged hypoxia (72 h) have greater mitoROS levels versus normoxic controls [ 29 ]. MitoROS within PAEC participate in Ca 2+ homeostasis as supported by data that higher intracellular Ca 2+ in PAECs from SU5416/hypoxia-induced PAH rats versus those from normoxic animals is acutely diminished by the mitochondria-targeted antioxidant MitoQ [ 113 ]. A recent study from our laboratory similarly employed the mitochondrial antioxidants MitoQ and MitoTEMPO to demonstrate that mitoROS production is greater in PASMCs from CH neonatal rats compared to normotensive animals and contributes to enhanced PA vasoconstriction following CH [ 114 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…Human PAECs exposed to prolonged hypoxia (72 h) have greater mitoROS levels versus normoxic controls [ 29 ]. MitoROS within PAEC participate in Ca 2+ homeostasis as supported by data that higher intracellular Ca 2+ in PAECs from SU5416/hypoxia-induced PAH rats versus those from normoxic animals is acutely diminished by the mitochondria-targeted antioxidant MitoQ [ 113 ]. A recent study from our laboratory similarly employed the mitochondrial antioxidants MitoQ and MitoTEMPO to demonstrate that mitoROS production is greater in PASMCs from CH neonatal rats compared to normotensive animals and contributes to enhanced PA vasoconstriction following CH [ 114 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…TRPV4 is a mechanosensor of the endothelial cells which can be activated by shear stress [26] , [44] , [45] . It mediates calcium influx and increases endothelial permeability [20] , [44] , [46] . To determine whether the TRPV4 mediated shockwave-triggerred BBB disruption, we administrated a TRPV4 antagonist, HC067047, via tail vein injection before shockwave treatment.…”
Section: Resultsmentioning
confidence: 99%
“…TRPV4 activation was shown to induce eNOS phosphorylation, to stimulate VEGF levels in the ischemic area and to up-regulate VEGFR2 expression (Chen et al, 2018). TRPV4-mediated extracellular Ca 2+ entry has been implicated also in neovascular diseases, such as PAH (Suresh et al, 2018) and cancer (see Section Remodeling of Endothelial TRP Channels Promote Aberrant Tumor Vascularization). Accordingly, preliminary work demonstrated that oxidative stress was able to dismantle endothelial permeability by stimulating the Src kinase Fyn to activate TRPV4 in human and mouse lung microvascular endothelial cells (Suresh et al, 2015).…”
Section: Trpv4 In Angiogenesismentioning
confidence: 99%
“…Accordingly, preliminary work demonstrated that oxidative stress was able to dismantle endothelial permeability by stimulating the Src kinase Fyn to activate TRPV4 in human and mouse lung microvascular endothelial cells (Suresh et al, 2015). Recently, it has been demonstrated that the higher levels of cytosol-and mitochondria-derived ROS led to the constitutive opening of TRPV4, thereby increasing resting [Ca 2+ ] i and promoting aberrant endothelial cell proliferation and migration (Suresh et al, 2018). This observation strongly suggests that endothelial TRPV4 is involved in PAH pathogenesis.…”
Section: Trpv4 In Angiogenesismentioning
confidence: 99%